2004
DOI: 10.1128/aac.48.6.1960-1967.2004
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial Spread of Ceftazidime-Resistant Klebsiella pneumoniae Strains Producing a Novel Class A β-Lactamase, GES-3, in a Neonatal Intensive Care Unit in Japan

Abstract: Klebsiella pneumoniae strain KG525, which showed high-level resistance to broad-spectrum cephalosporins, was isolated from the neonatal intensive care unit (NICU) of a Japanese hospital in March 2002. The ceftazidime resistance of strain KG525 was transferable to Escherichia coli CSH-2 by conjugation. Cloning and sequence analysis revealed that production of a novel extended-spectrum class A ␤-lactamase (pI 7.0), designated GES-3, which had two amino acid substitutions of M62T and E104K on the basis of the seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
50
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 40 publications
1
50
0
1
Order By: Relevance
“…The bacterial strains used in this study and the ␤-lactamases that they produce are shown in Table 1. The types of ␤-lactamase genes were previously confirmed by PCR analyses, cloning and sequencing experiments, as well as isoelectric focusing, as described elsewhere (6,10,15,25,36,40,42,43,44). APB, 3-nitrophenylboronic acid (NPB), and 2-thiopheneboronic acid (TPB) were purchased from Tokyo Kasei Kogyo Co., Ltd. (Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…The bacterial strains used in this study and the ␤-lactamases that they produce are shown in Table 1. The types of ␤-lactamase genes were previously confirmed by PCR analyses, cloning and sequencing experiments, as well as isoelectric focusing, as described elsewhere (6,10,15,25,36,40,42,43,44). APB, 3-nitrophenylboronic acid (NPB), and 2-thiopheneboronic acid (TPB) were purchased from Tokyo Kasei Kogyo Co., Ltd. (Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…GES (76,118,320,327,410,413,416,418), BES (45), TLA (8,369), SFO (240), and IBC (133,138,191,208,241,(410)(411)(412) are other examples of non-TEM, non-SHV ESBLs and have been found in a wide range of geographic locations.…”
Section: Veb-1 Bes-1 and Other Esblsmentioning
confidence: 99%
“…Although rare, GES enzymes have been identified worldwide, with reports from Greece, France, Portugal, South Africa, French Guiana, Brazil, Argentina, Korea, and Japan (25,33,42,86,90,155,164,168,173,186,(218)(219)(220). These enzymes have been most frequently associated with single occurrences.…”
Section: Plasmid-encoded Enzymes: Kpc and Gesmentioning
confidence: 99%